In vitro batch fermentation protocol to study the contribution of food to gut microbiota composition and functionality - Pérez-Burillo, Sergio; Molino, Silvia; Navajas Porras, Beatriz; Valverde Moya, Álvaro; Hinojosa Nogueira, Daniel; López Maldonado, Alicia; Pastoriza, Silvia; Rufián-Henares, José Ángel (Springer Nature, 2021)
Knowledge about the effect of foods on gut microbiota composition and functionality is expanding. To isolate the effect of single foods and/or single nutrients (i.e. fibre, polyphenols), this protocol describes an in vitro batch fermentation procedure to be carried out after an in vitro gastrointestinal digestion. Therefore, this is an extension of the previous protocol described by Brodkorb et al. (2019) about in vitro digestion. The protocol uses an oligotrophic fermentation medium with peptone, and a high concentration of fecal inocula from human fecal samples both to provide the microbiota and as the main source of nutrients for the bacteria. This protocol is recommended for screening work to be performed when many food samples are to be studied. It has been successfully used to study gut microbiota fermentation of different foodstuffs giving insights into their functionality, community structure, or ability to degrade particular substances, which can contribute to the development of personalized nutrition strategies. To carry out this procedure there is no need for a specific level of expertise. The protocol takes between 4 – 6 hours to prepare fermentation tubes and 20 hours of incubation.
Supplementary information The online version contains supplementary material available at https://doi.org/10.1038/s41596-021-00537-x. This version of the article has been accepted for publication, after peer review (when applicable) but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: http://dx.doi.org/10.1038/s41596-021-00537-x.
Keywords: Microbiota; Alimentos fermentados; In vitro fermentation; Gut microbiota; Food; Nutrients; Batch fermentation; In vitro digestion; Microbiome; Digestion; Personalized nutrition